The Effect of Influencer Credibility, Visual Content, and Viral Marketing on Purchase Decision of Wardah Cosmetics on Instagram - Vinni Wahyuni; Elkunny Dovir Siratan (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
In the face of intense competition in Indonesia's cosmetics industry, Wardah needs to implement effective marketing strategies through social media to enhance consumer purchase decisions. This study aims to examine the influence of influencer credibility, visual content, and viral marketing on cosmetic product purchase decisions on Instagram, both partially and simultaneously. A quantitative research method was employed, gathering data from 220 respondents via a questionnaire. Regression results revealed a coefficient of determination (R²) of 0.157, indicating that the independent variables explained 15.7% of the variance in purchase decisions. Partially, significant influences were found for Influencer Credibility (t = 2.923), Visual Content (t = 5.549), and Viral Marketing (t = 4.286) on purchase decisions. The F-test result showed a calculated F value of 8.193 > the F table value of 2.65, indicating a significant simultaneous effect. Hence, it can be concluded that influencer credibility, visual content, and viral marketing have a significant impact on consumer purchase decisions, both individually and collectively. This suggests that a marketing strategy leveraging these three variables can effectively boost cosmetic product purchases on Instagram.